2017
DOI: 10.1038/onc.2017.148
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 activation in endothelial cells is important for tumor metastasis via increased cell adhesion molecule expression

Abstract: Metastasis is a life-threatening feature of cancer and is primarily responsible for cancer patient mortality. Cross talk between tumor cells and endothelium is important for tumor progression and metastasis. However, very little is known about the mechanisms by which endothelial cells (ECs) that are close to tumor cells, respond to the tumor cells during tumor progression and metastasis. In this study, we exploited the use of EC-specific signal transducer activator of transcription 3 (STAT3) knockout mice to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 49 publications
1
47
0
1
Order By: Relevance
“…For distant metastasis, primary tumor cells must invade the stromal environment, intravasate, disseminate through blood vessels, colonize the distant site, and finally form metastatic nodules . Both tumor cells and endothelial cells are critical for tumor progression and metastasis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For distant metastasis, primary tumor cells must invade the stromal environment, intravasate, disseminate through blood vessels, colonize the distant site, and finally form metastatic nodules . Both tumor cells and endothelial cells are critical for tumor progression and metastasis …”
Section: Introductionmentioning
confidence: 99%
“…3 Both tumor cells and endothelial cells are critical for tumor progression and metastasis. 4 Numerous studies have shown that transforming growth factor beta (TGF-β)-mediated epithelial-to-mesenchymal transition (EMT) plays a crucial role in tumor invasion and metastasis. [5][6][7] Moreover, destruction of the vascular endothelial barrier is an important process through which cancer cells invade blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely involved in the process of cell proliferation, differentiation, apoptosis, and immune inflammation regulation, and is an important pathway of many cytokine signal transductions. 7,8 STAT3 plays an important role in pathological processes, such as inflammatory signaling and immunosuppression. STAT3 is certainly the most eminent among cancers and plays a vital role in regulating EMT during cancer progression.…”
Section: Dovepressmentioning
confidence: 99%
“…STAT3 can enhance the expression of matrix metalloproteinases (MMPs) that are responsible for the degradation of the basement membrane and extracellular matrix (ECM) in cancer invasion and metastasis. 8 Epithelial-mesenchymal transition (EMT) is a fundamental process by which cells change from epithelial-like state to a more mesenchymal-like phenotype. Thus, epithelial cells lose cell junction and gain the ability to invade and metastasize.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent activation of STAT3 was observed in many diseases characterized by chronic in ammation and brosis including SSc [26]. In endothelial cells STAT3 activation was mostly linked to increased expression of adhesion molecules including E-selectin, P-selectin and VCAM [43,44]. In our experiments OSM induced ICAM1 and junction plakoglobin JUP, however it did not affect expression of E-and P-selectin or VCAM.…”
Section: Discussionmentioning
confidence: 38%